"Trapped in an Empty Waiting Room"—The Existential Human Core of Loneliness in Old Age: A Meta-Synthesis. (January 2018) - Kitzmüller, Gabriele; Clancy, Anne; Vaismoradi, Mojtaba; Wegener, Charlotte; Bondas, Terese
Loneliness in old age has a negative influence on quality of life, health, and survival. To understand the phenomenon of loneliness in old age, the voices of lonely older adults should be heard. Therefore, the purpose of this meta-synthesis was to synthesize scientific studies of older adults' experiences of loneliness. Eleven qualitative articles that met the inclusion criteria were analyzed and synthesized according to Noblit and Hare's meta-ethnographic approach. The analysis revealed the overriding meaning of the existential human core of loneliness in old age expressed through the metaphor "trapped in an empty waiting room." Four interwoven themes were found: (a) the negative emotions of loneliness, (b) the loss of meaningful interpersonal relationships, (c) the influence of loneliness on self-perception, and (d) the older adults' endeavors to deal with loneliness. The joint contribution of family members, health care providers, and volunteers is necessary to break the vicious circle of loneliness.